Analysis of Combined Power and Refrigeration Generation Using the Carbon Dioxide Thermodynamic Cycle to Recover the Waste Heat of an Internal Combustion Engine. (2nd June 2014) - Wang, Shunsen; Bai, Kunlun; Xie, Yonghui; Di, Juan; Cheng, Shangfang
Abstract : A novel thermodynamic system is proposed to recover the waste heat of an internal combustion engine (ICE) by integrating the transcritical carbon dioxide (CO2 ) refrigeration cycle with the supercritical CO2 power cycle, and eight kinds of integration schemes are developed. The key parameters of the system are optimized through a genetic algorithm to achieve optimum matching with different variables and schemes, as well as the maximum net power output (W net ). The results indicate that replacing a single-turbine scheme with a double-turbine scheme can significantly enhance the net power output (W net ) and lower the inlet pressure of the power turbine (P 4 ). With the same exhaust parameters of ICE, the maximum W net of the double-turbines scheme is 40%–50% higher than that of the single-turbine scheme. Replacing a single-stage compression scheme with a double-stage compression scheme can also lower the value of P 4, while it could not always significantly enhance the value of W net . Except for the power consumption of air conditioning, the net power output of this thermodynamic system can reach up to 13%–35% of the engine power when it is used to recover the exhaust heat of internal combustion engines.